A brief history of Nordic Walking - Marta Anna Zurawik (Kazimierz Wielki University, 2016)
Walking is a popular form of exercising, because it is inexpensive, safe, and accessible form of physical activity that be performed in various environments. Nordic walking, also known as walking with poles or fitness walking is an activity that uses specially designed walking poles to engage a whole body in a workout. The early developments of the activity are linked to Finnish governmental actions in 1960's and then commercial endeavours in the USA and Finland in 1990's in order to improve health of sedentary populations. Five decades later Nordic walking is a popular exercise and leisure activity promoted to general public in many countries around the world.